The level of The Utilization of Main Facilities of Birea Fish Landing Base, Bantaeng Regency - Darma, Darma; Safruddin, Safruddin; Mallawa, Achmar (Torani Journal of Fisheries and Marine Science, 2020)
This study aims to identify main facilities and determine the level of the main facilities utilization of Birea fish landing base, Pa'jukukang District, Bantaeng Regency. The research was conducted from May to July 2020. The method used in this research is a case study. Primary data was consisting of the length of the pier, the distance between ships, the length of time to moor, the length of the breakwater and the length of the trip, and the size and number of ships anchored, were collected through direct observation in the field. Meanwhile, secondary data such as catch production data, development of the number and types of fishing units, the size of the port pool area, and the depth of the waters were taken through the interviews method. The utilization rate of the main facilities utilization of Berea fish landing base are a pier utilization rate of 90.5%, a port pool of 72.5%, a land port 86%, and two meters of water depth are required. Based on the research results, it is found that the long pier is still possible to accommodate ships that are anchored, while the port pool and portland still meet the requirements, however, dredging is necessary for dredging the depth of the waters for shipping in and out of ships. Key words: birea fish landing base, the level of main facilities utilization, bantaeng regency.